A porous media approach for plantar tissue during gait. Issue 1 (21st October 2015) - Boso, Daniela P.; Sciumè, Giuseppe; Pizzocaro, Mattia; Schrefler, Bernhard A.
Abstract Recently a new computational model, based on the thermodynamically constrained averaging theory, has been proposed to predict tumor initiation and proliferation and afterwards to study plantar tissue mechanics. The foot tissue is modeled as an elastic porous medium, in large strain regime and completely filled by a fluid phase. By considering the interstitial fluid, it is possible to mimic the viscoelastic behavior of the plantar tissue observed experimentally. Being the global response of the bi‐phase system viscoelastic, it is shown that the duration of stance as well as of each of gait cycle has an influence on tissue stress field. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)